Clinical outcomes among patients with extreme obesity undergoing elective coronary revascularization: Evaluation of major complications in contemporary practice. (1st May 2015) - Ramirez, F. Daniel; Hibbert, Benjamin; Simard, Trevor; Maze, Ronnen; Pourdjabbar, Ali; Chong, Aun-Yeong; Le May, Michel; Shiau, Judy; Wilson, Kumanan R.; Hawken, Steven; O'Brien, Edward R.; So, Derek Y.; et al.
Abstract: Background/objectives: Individuals with extreme obesity (EO), defined by a body mass index (BMI) ≥ 40 kg/m 2, constitute an increasingly prevalent population at higher risk of procedural complications. The implications of increasing weight burdens among this subset of patients in the setting of elective coronary revascularization have yet to be adequately studied. Methods: We sought to define major complications in this group at one year following contemporary revascularization strategies by retrospectively analysing a cohort of consecutive EO patients undergoing elective percutaneous coronary intervention (PCI) or coronary artery bypass surgery (CABG). The primary endpoint was a composite of peri- and post-procedural complications. Secondary endpoints included a cardiovascular composite and target vessel revascularization (TVR). Results: Adjusted event-free survival curves for the primary endpoint among 133 patients differed significantly with higher BMI (> 43.2 kg/m 2 ) associated with greater risk ( p  = 0.02). The primary endpoint occurred more frequently with CABG compared to PCI (24.2% vs. 5.0%, p  < 0.01), which remained significant after adjusting for differences in baseline variables. Rates of the cardiovascular composite and TVR were comparable. Conclusions: Increasing BMI was associated with greater risk for major complications among EO patients undergoing elective coronary revascularization. PCI was associated with fewer complications; however, both revascularization strategies demonstrated equivalent rates of death, MI, and/or stroke. Larger studies may permit a better understanding of the associations between increasing BMI and specific outcomes and to evaluate the role for pre-procedural weight loss in this select population. Highlights: We focus on extremely obese (EO) patients' post-elective coronary revascularization. We describe the risk profile of this population based on outcome data at one year. We report an incremental risk of complications with higher BMI within this group. The role for pre-procedural weight reduction in this setting warrants further study.